PELATIHAN SENI DALAM RANGKA MENGGALI DAN MENGEMBANGKAN POTENSI KESENIAN DAN WISATA DI DESA GONDOSULI KABUPATEN TEMANGGUNG - Henry Cholis (Abdi Seni, 2020)
Gondosuli Village is one of the villages in Temanggung Regency that have a thick background of customs and culture. The majority of the population are Muslims, farmers and some trade. Village with historical footsteps with the ancient heritage of Gondosuli Temple in the middle of the village. The art in Gondosuli village once succeeded but now it doesn’t exist and fades away. Gondosuli village with all its uniqueness, natural beauty, ancient relics and artistic potential. These potentials are of course possible to be a hope and goal to make Gondosuli Village a tourist village. Dedication to society (PPM) is an activity that seeks to encourage Gondosuli Village to move towards a tourist village even though it is only a small and initial step. The method used is observation, design of activities and design, training (workshops), and application activities. The main objective of the method is to strengthen the identity of tradition and cultural arts. The initial step of the new dedication to society is at the stage of building a village image (branding) through promotional media and information.Keywords: Gondosuli Village, Branding, Tourist Destinations